Strategic delegation and international capital taxation - Matthias Brückner (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2001)
The literature on tax competition generally concludes that international coordination of capital taxes among symmetric countries increases tax rates. This paper investigates whether this conclusion also holds in a political economy framework where taxes are set by elected policy makers. It shows that policy makers are fiscally more liberal than the average citizen if taxes are set non-cooperatively. However, fiscally more conservative policy makers are elected if taxes are set cooperatively. The introduction of tax coordination cannot remove the incentive to compete for foreign capital, but simply shifts it to the election stage. The paper proves that with standard specifications of the utility functions, coordination leads to lower tax rates than competition.
Keywords: H2; 330; Tax competition; tax coordination; strategic delegation; Kapitalertragsteuer; Steuerwettbewerb; Steuerharmonisierung; Ökonomische Theorie der Demokratie; Median Voter